Studi Pengaruh Temperatur terhadap Laju Erosi-Korosi Baja API 5CT L80 dan API 5L X60 pada Lingkungan CO2 dan Asam Asetat - Bambang Widyanto; Anthonius Valentino; Abdullatief Zuhdy (Jurnal Metalurgi dan Material Indonesia, 2019)
In this study, test was conducted to determine the effect of temperature with CO2 and acetic acid environment on the corrosion rate of API 5CT L80 and API 5L X60 steel pipe. Corrosion immersion test was held using modified pressurized autoclave which allow movement in testing fluid to simulate erosion condition. Each test conducted for 168 hours with 2 bar of pressurized CO2 in the system, testing fluid with 3360 ppm acetic acid concentration and four variation of temperature which are 40˚C, 60 ˚C, 80 ˚C and 95 ˚C. Immersion test on API 5L X60 steel specimen as regard to increase of temperature will also increase the value of corrosion rate, mean test on API 5CT L80 steel sample have different corrosion rate trend. Temperature increase from 40 ˚C to 60 ˚C on API 5CT sample will increase the value of the corrosion rate, on the other hand increasing the temperature from 60 ˚C to 80 ˚C will cause the corrosion rate to decrease. The highest value of the corrosion rate on API 5CT L80 observed on 95 ˚C. The value of the corrosion rate each temperature are influenced by the layer of corrosion product formed on the surface of the specimens which analyzed by using scanning electron microscope (SEM) and x-ray diffraction (XRD).